2022
DOI: 10.3389/fped.2022.978661
|View full text |Cite
|
Sign up to set email alerts
|

Parents' intention for their children to receive COVID-19 vaccine: Implications for vaccination program in Macao

Abstract: IntroductionThe decision about vaccinating children is subject to their parents' decision. To inform strategies that support full vaccination coverage, it is important to understand the parents' vaccination attitude and tendency to act. This study aims to investigate the intention and the factors affecting parents' decision-making about vaccinating their children.MethodsA cross-sectional, self-administered online questionnaire was completed by parents of children aged 3–12 yeas in Macao between 7 March and 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 80 publications
2
11
0
2
Order By: Relevance
“…Both studies found all constructs, attitudes, subjective norms, and perceived behavioral control to be related to intention. Conversely, a study conducted in China after the authorization for COVID‐19 vaccines among children showed similar results to ours and did not find perceived behavioral control to be indicative of parents' intentions 31 . Based on our findings and the previous research, we can conclude that perceived behavioral control is important for caregivers when vaccines are not accessible for their child.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Both studies found all constructs, attitudes, subjective norms, and perceived behavioral control to be related to intention. Conversely, a study conducted in China after the authorization for COVID‐19 vaccines among children showed similar results to ours and did not find perceived behavioral control to be indicative of parents' intentions 31 . Based on our findings and the previous research, we can conclude that perceived behavioral control is important for caregivers when vaccines are not accessible for their child.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, background variables (e.g., sociodemographic characteristics) only indirectly influence intention through attitudes, subjective norms, and perceived behavioral control. The TPB has been applied to study different health behaviors, including COVID‐19 vaccination decisions among adults 27–29 and parents for their children in the general population 29–32 . We aimed to use the TPB to identify antecedents contributing to caregivers' decision to vaccinate young CCS against COVID‐19, including health literacy related to COVID‐19 aspects (referred to as “COVID‐19 health literacy” hereafter) and frequency of COVID‐19 information‐seeking.…”
Section: Introductionmentioning
confidence: 99%
“… 27 Studies show that parents are most concerned about the serious side effects that are associated with the COVID-19 vaccine. 12 Possible causes of the vaccine’s hesitancy may have been the vaccine’s newness and a lack of strong evidence of its safety. In Uganda, requiring written consent may cause anxiety among those planning to get vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Studies on parents’ readiness to vaccinate their children against COVID-19 have been conducted, revealing inconsistent results. 11 , 12 In Japan, close to 60% of parents remained hesitant to vaccinate their children against COVID-19, 10 in Turkey, 56.8% of parents were willing to vaccinate their children, 13 in Saudi Arabia, 52% were hesitant to vaccinate their children, 14 in the UK, approximately 48% of the participants were willing to vaccinate their children. 15 In Italy, 10% of the participants were hesitant about immunization.…”
Section: Introductionmentioning
confidence: 99%
“… 23–28 However, with strong educational efforts by health experts and authorities, there was an increase in the quality of knowledge 15 and consequently, COVID-19 vaccine uptake. 28 Previous studies have associated formal knowledge of COVID-19, adherence to COVID-19-related policies, and vaccination intentions. 15 , 28 A previous study also revealed that cogent information on COVID-19 vaccine helped increase parents’ intentions to vaccinate their children.…”
Section: Introductionmentioning
confidence: 99%